Desalination of seawater using an electrode modified with poly(3, 4-ethylenedioxythiophene). (November 2019) - Salgado, R; Arteaga, G C; Romero, M; Martínez, J; Ramos, A; Burgos, R; García, C
Abstract: The procedure for obtaining electrodes modified with poly(3, 4-ethylenedioxythiophene) has been widely studied for its multiple applications. This study evaluates the potential contribution of electrodes modified with poly(3, 4-ethylenedioxythiophene) for desalination of seawater. Potentiostatic electropolymerization of 3, 4-ethylenedioxythiophene was conducted on 6 cm 2 steel electrodes by using a supporting electrolyte consisting of lithium perchlorate in acetonitrile. This modified electrode was used in the extraction of anions and cations from samples of synthetic seawater by means of 20 extraction cycles (optimal cycles) and using a combination of p-type and n-type doping. A total of 140 extractions (number of optimal extractions) were carried out, which led to desalination of synthetic seawater by about 80-90%, as evidenced by the decrease in the conductivity of the solution containing the ions. Therefore, this procedure could become an alternative for seawater desalination.